Pengaruh Kepemilikan Institusional, Enterprise Risk Management, dan Komisaris Independen terhadap Integritas Laporan Keuangan Dimoderasi Kualitas Audit - Sitorus, Riris Rotua; Tambun, Sihar; Kurniawan, Steven (Universitas 17 Agustus 1945 Jakarta, 2025)
The main objective of this study is to determine the direct impact of institutional ownership, enterprise risk management, and independent commissioners on the integrity of financial statements. Additionally, this study aims to provide recent empirical evidence regarding the role of audit quality in strengthening the influence of institutional ownership, enterprise risk management, and independent commissioners on financial statement integrity. The sampling method used in this study is purposive sampling, involving companies in the property and real estate sector listed on the Indonesia Stock Exchange from 2020 to 2024, with a total sample size of 125. The test results indicate that institutional ownership has a positive effect on the integrity of financial statements, while enterprise risk management and independent commissioners do not significantly affect financial statement integrity. Furthermore, audit quality as a moderating variable is able to moderate the relationship between enterprise risk management and financial statement integrity. However, audit quality does not moderate the influence of institutional ownership and independent commissioners on financial statement integrity.